Influence of Learning Strategies STAD Using Portfolio Assessment and Academic Ability to Concept Training Junior High School Students in Biology Education - Puspani Puspani (Pascasarjana Universitas Negeri Malang (UM), 2013)
Pengaruh Strategi Pembelajaran STAD Menggunakan Penilaian Portofolio dan Kemampuan Akademik terhadap Pemahaman Konsep Siswa SMP pada Pembelajaran Biologi Abstract: This study is a quasi-experimental research (quasi experimental) which aims to: (1) examine the effect of STAD learning strategies using a portfolio assessment to the understanding of concepts and critical thinking skills, (2) test the effect of academic ability to understanding of concepts and critical thinking skills students, (3) test the interaction effect of STAD strategy using portfolio assessment and academic ability to the understanding of concepts and critical thinking skills of students. Research using the draft